Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1)
=3(x-y)+(x-y)(x+y)
=(x-y)(3x+3y)
2)
=x^2+2x+x+2
=x(x+2)+x+2
=(x+1)(x+2).
\(3x-3y+x^2-y^2\)
\(=3\left(x-y\right)+\left(x-y\right)\left(x+y\right)\)
\(=\left(x-y\right)\left(3+x+y\right)\)
\(x^2+3x+2\)
\(=x^2+2x+x+2\)
\(=x\left(x+2\right)+\left(x+2\right)\)
\(=\left(x+1\right)\left(x+2\right)\)
3x2-3y2-2(x-y)2
=3(x2-y2)-2(x-y)2
=3(x-y)(x+y)-2(x-y)(x-y)
=(x-y)(3x+3y-x+y)
=(x-y)(2x+4y)
=2(x-y)(x+2y)
3x^2 +3y^2 -6xy -12
=3(x^2 - 2xy +y^2 - 2^2 )
=3 (x-y)^2 - 2^2
=3(x-y-2)(x-y+2)
3(x+y) -(x^2+2xy+y^2)
=3(x+y) -(x+y)^2
(x+y)(3-x-y)
\(x^2-2xy+y^2+3x-3y-10=\left(x^2-2xy+y^2\right)+3\left(x-y\right)-10=\left(x-y\right)^2+3\left(x-y\right)-10=\left(x-y\right)^2-2\left(x-y\right)+5\left(x-y\right)-10=\left(x-y\right)\left(x-y-2\right)+5\left(x-y-2\right)=\left(x-y+5\right)\left(x-y-2\right)\)
= ( x - y)^2 - 3 ( x - y) . -10
= ( x - y)^2 - 2.(x-y) . 3/2 +9/4 - 49/4
= ( x - y - 3/2) ^2 - (7/2)^2
= ( x- y - 3/2 - 7/2 )( x - y -3/2 + 7/2 )
=( x - y - 5 )( x - y + 2)
= ( x - y)^2 - 3 ( x - y) . -10
= ( x - y)^2 - 2.(x-y) . 3/2 +9/4 - 49/4
= ( x - y - 3/2) ^2 - (7/2)^2
= ( x- y - 3/2 - 7/2 )( x - y -3/2 + 7/2 )
=( x - y - 5 )( x - y + 2)
LÀm thế này đúng không cho nhận xét
\(x^2-2xy+y^2+3x-3y-10\)
\(=\left(y^2-xy-5y\right)-\left(xy-x^2-5x\right)+\left(2y-2x-10\right)\)
\(=y\left(y-x-5\right)-x\left(y-x-5\right)+2\left(y-x-5\right)\)
\(=\left(y-x+2\right)\left(y-x-5\right)\)
\(3x-3y+x^2-y^2\)
\(=\left(3x-3y\right)+\left(x^2-y^2\right)\)
\(=3\left(x-y\right)+\left(x-y\right)\left(x+y\right)\)
\(=\left(x-y\right)\left(x+y+3\right)\)